First-principles simulation of active site selectivity for CO2 and H2 adsorption on Mg(OH)+/Mg2+ and Ca(OH)+/Ca2+ zeolites - Samal, Pragnya Paramita; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2024)
One very effective strategy for addressing global warming and transitioning to sustainable energy sources is selective CO2 separation over H-2. Porous materials, particularly zeolites, have demonstrated enormous potential for energy-efficient separation techniques combined with storage. By altering interactions at cation-binding sites, zeolite's gas adsorption characteristics toward carbon capture can be improved. In this study, Mg and Ca are assessed as extra-framework cations in divalent (Ca2+, Mg2+) and monovalent states (Ca(OH)(+), Mg(OH)(+)) in faujasite and chabazite zeolites for CO2 capture over H-2. The study also explores the impact of mixed cations, viz., a combination of both Ca2+ and Mg2+ in the framework, on their selective adsorption potential. This study uses DFT with dispersion corrections to calculate adsorption energies, enthalpies, and Gibb's free energies of adsorbed CO2 and H-2 molecules. Among the dispersion parameters evaluated, viz., D4, TS/HI, and MBD, D4 approaches experimental accuracy. In general, the adsorption trend obtained for CO2 is Mg FAU > Ca FAU > Mg CHA > Ca CHA > Mg(OH)(+) FAU > Ca(OH)(+) FAU > Mg(OH)(+) CHA > Ca(OH)(+) CHA. The heats of adsorption using PBE+D4 for CO2 are -46 kJ/mol for Ca FAU and -10 kJ/mol for Ca(OH)(+) FAU, respectively. These values closely align with the experimental results of -45 and -6 kJ/mol, respectively, within a chemical accuracy limit of +/- 4 kJ/mol. The relative adsorption energies suggest that for both FAU and CHA, there exists a minimum difference of 26 kJ/mol in adsorption energies between CO2 and H-2. Hence, this piece of work highlights that FAU with Ca and Mg as extra-framework cations in a six-membered cage can be a viable substitute to replace, the current best candidate in literature, viz., Li+, for selective CO2 capture.